KAJIAN FEMISIDA DALAM PERSPEKTIF GENDER SEBAGAI DAMPAK DARI BUDAYA PATRIARKI - yuliana kemalasari, ni putu (VYAVAHARA DUTA, 2025)
A crime committed by making women as objects or victims, is often associated with patriarchal culture. This form of crime is known as femicide or feminicide. Femicide can be interpreted as an act of intentional murder of women because they are women. This phenomenon is an important study material considering that the patriarchal culture in society is considered as one of the things that triggers the emergence of femicide. This study will focus on the crime of femicide associated with a gender perspective which is studied from a patriarchal cultural perspective. To answer this problem, this study uses a normative juridical method that will focus on primary legal sources, namely library materials that will provide answers to how patriarchal culture influences femicide from a gender perspective. With this research, it is hoped that it can provide input on how patriarchal culture can have a major impact on social life in society to the point of giving birth to gender-based understandings and actions including femicide.